PENGARUH MINAT BELAJAR DAN KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS V SEKOLAH DASAR DI GUGUS DEWI SARTIKA JAKARTA UTARA - Mochammad Hasbi As Shidiqi; Karta Sasmita; Suratinah . (Institut Pendidikan Tapanuli Selatan, 2022)
This study aims to analyze the effect of learning interest and Emotional Intelligence on the mathematics learning outcomes of fifth grade elementary school students in the Dewi Sartika cluster North Jakarta. The definition of learning outcomes in this study is the acquisition of the student’s learning process in accordance with the objectives of teaching mathematics, especially on the material of blocks and cubes in the cognitive domain. Learning interest refers to the feeling of preferring one thing over another, participating and being active in teaching and learning activities, being enthusiastic, liking, interested, and paying attention during the mathematics learning process. Emotional Intelligence or EQ is a series of personal abilities in students to control their emotions and recognize their feelings as well as the feelings of other individuals. This study uses a quantitative approach with a survey method. The researcher took samples using the Non Probability Sampling technique with the type of Purposive Sampling. The sample of this research is 140 students of the fifth graders. The instruments used are questionnaire and test. Data analysis used in this study is multiple linear regression. The results showed that (1) Interest in learning had a significant influence on the mathematics learning outcomes of fifth grade elementary school students in the Dewi Sartika cluster North Jakarta. The results showed that learning interest contributed 18,2533% to student’s mathematics learning outcomes. (2) Emotional intelligence had a significant influence on the mathematics learning outcomes of fifth grade elementary school students in the Dewi Sartika cluster North Jakarta. The results showed that emotional intelligence contributed 54,7867% to student’s mathematics learning outcomes, (3) Learning interest and emotional intelligence had a significant influence on mathematics learning outcomes of fifth grade elementary school students in the Dewi Sartika cluster North Jakarta. The results showed that learning interest and emotional intelligence contributed 73,04% to student’s mathematics learning outcomes. Students who have a learning interest and high emotional intelligence will improve their mathematics learning outcomes and vice versa. Meanwhile, 26,96% of mathematics learning outcomes are influenced by other factors such as intellectual intelligence, learning media, teaching aids, learning models, facilities, parental support and so on. The results of this study can be used as a reference for parents, teachers, and schools who want to get maximum student learning outcomes in mathematics.